(untitled) (Ustozlar uchun, 2024)
This article offers a comprehensive examination of Learning Management Systems, specifically Canvas, that supports university students, teachers, and researchers in coordinating learning and teaching activities. Proposing the implementation of this type of LMS in Uzbekistan would be beneficial, as recommended. This article provides a comprehensive analysis of the Learning Management System (LMS) and highlights the significance of Canvas in improving students' academic writing abilities. Uzbekistan's universities should consider implementing Canvas to better support students, professors, and researchers.